Response to the Editor - Ai (JRI, 2010)
Dear Editor, Regarding the questions raised and comments made on the paper authored by me "Secretion of Vascular Endothelial Growth Factor in a Three-Dimensional Culture of Human Endometrium; an In-Vitro Model for Endometriosis" I have provided the following response for more clarification.